Pig systems in Asia and the Pacific: how can research and development enhance benefits to the poor? - Thorpe, W.R.; Jemaneh, T. (International Livestock Research Institute, 2008)
This workshop was conducted to address the importance of pig keeping to the livelihoods of millions of poor people in Asia and the Pacific particularly in Southeast Asia. It deals with questions like - what is the role of research and of the research and development (R & D) community in ensuring that the poor benefit? And if researchable issues are addressed and development interventions identified, what are the best ways of ensuring that the answers are applied as quickly and effectively as possible? Drivers of change that affect pig systems and the poor in Asia were identified and discussed and emerging issues and new ways of working in the R&D community were identified. These sources of innovation and change were discussed in the context of development outcomes that directly affect the poor. The report is organized in three parts, viz, pig systems, livelihoods and poverty; facilitating interventions and innovation in production systems and markets; and facilitating innovation in R&D institutions and knowledge management.